Moke sebagai Instrumen Rekonsilisasi dan Identitas Budaya: Analisis Fungsi Sosial Masyarakat Desa Nawang Kewa - Trisnawati Bura; Katharina Woli Namang; Yeremias Bardi (Jurnal Pendidikan, Bahasa dan Budaya, 2026)
This study examines moke as a cultural instrument of reconciliation and identity within the community of Nawang Kewa Village, Sikka Regency. The research is grounded in the concern over the shifting meaning of moke due to modernization and globalization, which potentially weakens its cultural and social significance. The objective of this study is to analyze the social functions, symbolic meanings, and the role of moke as a reconciliation mechanism in resolving social conflicts. This research employs a qualitative approach with a descriptive-interpretative and ethnographic design. Data were collected through in-depth interviews, participatory observation, and documentation, involving traditional leaders, moke producers, and younger community members. The findings reveal that moke functions in three main dimensions: as a ritual-sacred symbol in traditional ceremonies, as a social-integrative medium that strengthens solidarity and communication, and as a socio-reconciliative instrument in conflict resolution through symbolic peace practices. Furthermore, the study identifies a shift in meaning among younger generations, where moke tends to be perceived more as a consumptive product rather than a cultural symbol. The implications of this research highlight the importance of preserving local cultural values through intergenerational transmission and strengthening customary institutions to maintain social cohesion and cultural identity.